Empirical Antibiotics in Non-Ventilated Cases of Meconium Aspiration Syndrome - Sung-Min Kang; Chae-Ku Jo; Sun-Young Lee; Myo-Jing Kim (Korean Society of Neonatology, 2019)
Purpose Meconium aspiration is assumed to be a risk factor for bacterial infection, and patients with meconium aspiration syndrome (MAS) are commonly treated with empiric antibiotics in clinical settings. However, little is known about the effectiveness of the empirical antibiotics treatment. Here, we compared the short-term clinical outcomes associated with empirical antibiotics treatment in non-ventilated cases of MAS. Methods A retrospective study was conducted on infants admitted with non-ventilated cases of MAS from March 2008 to September 2016. The infants enrolled in the study were divided into two groups based on the antibiotics treatment, and their clinical outcomes were compared. The incidence of sepsis during the hospitalization period and the incidence of delayed sepsis up to 3 months were evaluated. The effects of empirical antibiotic use on respiratory symptoms were evaluated, and the complications were compared. Results A total of 109 infants were evaluated, of which 61 (56.0%) received antibiotics and 48 (44.0%) did not receive antibiotics. No differences in clinical characteristics were noted between the two groups. However, the empirical antibiotics group showed a significantly higher mean of respiratory rates, C-reactive protein levels, and positive rates, as well as a significantly longer hospitalization period. In clinical outcomes, there were no differences in sepsis rates or respiratory support duration. Furthermore, there were no differences in complications. Conclusion The empirical use of antibiotics did not affect the clinical outcomes in cases of non-ventilated MAS. The role of empirical antibiotics in these infants may need to be reevaluated.